The Impact of Monetary adn Fiscal on Poverty in Indonesia: Analyze Error Correction Model - Al Bina (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This research aims to analyze the impact of monetary and fiscal policy on poverty in Indonesia using the estimation method error Corretion model. The data analysis used uses secondary data from the agency a Indonesian statistics and banking center. The research results show Economic growth has a significant negative impact on Indonesia poverty monetary policy has a significant negative impact against poverty. fiscal policy has an insignificant impact on poverty, exchange rates and inflation have a significant positive impact on poverty in Indonesia. Poverty reduction in Indonesia is dominated by monetary policy.